Experimental investigation of eco-friendly cryogenic minimum quantity lubrication (CMQL) strategy in machining of Ti–6Al–4V thin-wall part. (10th July 2022) - Wu, Ge; Li, Guangxian; Pan, Wencheng; Raja, Izamshah; Wang, Xu; Ding, Songlin
Abstract: The application of cutting fluid is the most direct and effective method for improving the productivity in machining difficult-to-cut materials. Besides the typical flood cooling method, advanced and eco-friendly solutions such as minimum quantity lubrication (MQL) and cryogenic minimum quantity lubrication (CMQL) have been applied in green manufacturing processes to avoid the environmental and health issues associated with conventional cutting fluid. High-efficiency machining of thin-wall components is of significant importance to the aerospace and defence industries. However, the effects of CMQL in the thin-wall milling process have not been investigated, and the mechanisms of tool wear, chip evolution, stress distribution and part deformation are still unclear. To address this gap, this paper presents the investigation and corresponding analysis of CMQL in the machining of titanium thin-wall components. Comparative experiments were carried out under different cutting environments, including flood cooling, MQL and CMQL machining. The tool wear state, cutting force, chip morphology, surface quality and workpiece deformation were compared and analysed. Experimental results show that CMQL machining can significantly lower the cutting loads and deformation values of thin-wall parts, especially at higher spindle speed. Compared with flood and MQL machining, CMQL machining led to approximate 28.5% and 31.2% smaller cutting force at the spindle speed of 4500 rpm, and the maximum deformation in CMQL machining was decreased by 41.4% and 44.7%, respectively. Meanwhile, the wear resistance of the cutting tool and surface quality is enhanced in comparison with flood cooling and MQL machining. It was shown that the machined surface under CMQL condition exhibited 34.5% and 45.8% lower surface roughness ( R a ) compared to flood and MQL machining at the highest spindle speed. Overall, the experimental outcomes demonstrate the feasibility of CMQL in improving the machinability of thin-wall components made from difficult-to-cut material, owing to its superior lubrication and cooling functions. The cryogenic cooling action and induced thermal effect are especially beneficial to controlling the flexible deformation. Highlights: CMQL machining can efficiently inhibit both the adhesion and abrasion wear on the tool rake and flank surfaces . The resultant cutting force decreases when the CMQL temperature is lower, especially at higher cutting speeds. In CMQL machining, the surface integrity is greatly improved. In CMQL machining of thin-wall components, the cold medium can lead to lower deflection values.